Analisis SWOT Sebagai Dasar Pemasaran Produk Air Minum Kemasan “Blit” Perumdam Tirta Penataran Kabupaten Blitar - Anggelia Hayuning Ariffa; Mega Cattleya P.A Islami (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Perumdam Tirta Penataran Blitar Regency is a regional water company operating in Blitar. Where this company has good water sources that must be utilized, namely bottled drinking water (AMDK). With abundant springs, this innovation must be carried out as company development. With the SWOT analysis method, it is hoped that this research can provide an answer or solution to the innovation development carried out by Perumdam Tirta Penataran, Blitar Regency. Where the results obtained from the SWOT analysis through a questionnaire are IFAS of 2.23 and EFAS of 1.59, where the figures obtained are in quadrant 1, which opens up a wide opportunity to make Blit AMDK products better known to the public by utilizing the product's strengths. . Then continue with the aggressive strategy analysis with a marketing mix that is in accordance with AMDK Blit which can be used as a promotional method in the future when the product has been marketed publicly to the general public so that the strength of Perumdan Tirta Penataran Blitar Regency is expected to pay attention to, strengthen and maximize services so that potential consumers can interested in AMDK Blit products. It is hoped that with the above methods and the analysis carried out by AMDK at Perumdam Tirta Penataran it can develop further in the future.